Fathom out: biogeographical subdivision across the Western Australian continental margin – a multispecies modelling approach. Issue 12 (5th August 2013) - Woolley, Skipton N. C.; McCallum, Anna W.; Wilson, Robin; O'Hara, Timothy D.; Dunstan, Piers K.
Abstract: Aim: Biogeographical regions are often used as a basis for management strategies, yet a challenge for biodiversity management across broad scales is establishing biogeographical regions that are robust across taxonomic groups. Methods: Finite mixture models were developed to predict multiple species assemblages termed archetypes. Modelled species archetypes were developed using Decapoda, Ophiuroidea and Polychaeta species, which were grouped based on their similar responses to oceanographic and geographical gradients. Location: Outer‐shelf and slope (50–1200 m) of the continental margin of Western Australia ( 11° S–36° S). Results: Four faunal regions were defined based on cross‐taxa surrogates grouped as archetypes. These faunal regions were defined by oxygen, salinity, carbon and temperature gradients across latitude and bathymetry. Two broad latitudinal bands and two bathyal regions were described. Adjacent faunal groups were not defined by abrupt geographical breaks but rather transitions. Main conclusions: These results suggest that faunal distributions were less finely resolved than existing marine bioregions on the Western Australian continental margin and that environmental gradients are correlated with distributions of benthic marine invertebrates. Identifying biogeographical regions based on these methods has the potential to inform management across a broad range of environments.